Musical Interpretations Of Amor, Se Vuo’ Ch’i’torni Al Giogo Anticho By Petrarch in Canzones by Bartolomeo Tromboncino, Bernardo Pisano and Sebastiano Festa - Elena V. Pankina (Современные проблемы музыкознания)
The development of poetic Petrarchism in the first decade of the 16th century entailed the flourishing of Petrachism in music. During the transformation of poetic and musical composition due to the development of madrigal, musicians resorted to Petrarch’s poems as a way to free themselves from the dictate of normative song forms and language and to find new ways of musical expression. Among them are Bartolomeo Tromboncino, Bernardo Pisano, and Sebastiano Festa and their focus on Petrarch’s canzone Amor, se vuo’ ch’i’torni al giogo anticho. All the works were published within a short time span. The earliest is the canzone by Tromboncino, included in the Eleventh Book of Frottole by Ottaviano Petrucci (Fossombrone, 1514). Next came Pisano with a work from his author’s collection, also published by Petrucci (Venice, 1510). Finally, the composition of Festa became part of the First Book of Frottole, published by Giovanni Giacomo Pasoti and Valerio Dorico (Rome, 1526). In all the three cases the first stanza of the Petrarch’s canzone is set to music. Tromboncino’s version clearly shows the reliance on the frottola style and the possibility of a solo performance by cantore al liuto. Pisano creates a canzone-motet in a sublime contrapuntal style with a deep intonationbased elaboration of the text. Festa’s interpretation is based on his experience as a church musician. He has a penchant for complex texture, yet, in general, opts for a declamatory presentation of the text. In this way, the three stylistic interpretations of Petrarch’s canzone reflect both the creative individuality of each author and the general evolutionary trends of the first decades of the Cinquecento and its concepts about high secular vocal composition.